Accommodation response for integral photography still images - Park, Min-Chul; Yano, Sumio (THREE-DIMENSIONAL IMAGING, VISUALIZATION, AND DISPLAY 2015, 2015)
In this paper the accommodation responses for integral photography still images were measured. The experimental results showed that the accommodation responses for integral photography images showed a linear change with images showing the depth position of integral photography, even if the integral photography images were located out of the depth of the field. Furthermore, the discrimination of depth perception, which relates to a blur effect in integral photography images, was subjectively evaluated for the examination of its influence on the accommodation response. As a result, the range of the discrimination of depth perception was narrow in comparison to the range of the rectilinear accommodation response. However, these results were consistent according to the propensity of statistical significance for the discrimination of depth perception in the out range of subjectively effective discriminations.